Knowledge, attitudes and practices on Papanicolaou cervical smear - Bazán, Fernando (2007)
Objetives: To determine the level of knowledge, attitudes and practices with respect to the Papanicolaou cervical smear test (Pap), to find association between age and learning level, and to describe the characteristics on Pap’s periodic practice. Design: Analytical and cross-sectional study. Setting: San Bartolome Mother and Child National Teaching Hospital. Patients: Women in fertile age. Interventions: Structured questionnaire, self-developed, from November 2005 through January 2006. X2 , t student, Anova and OR were used for statistical analysis. Main outcome measures: Level of knowledge, attitudes and practices on Papanicolaou smear, as well as associations and characteristics on its periodical practice. Results: Of 501 surveys, 63% showed low level of knowledge, 66% had an unfavorable attitude, and 71% an incorrect practice of Pap smear; OR between knowledge level and correct practice was 1,45 (IC = 0,98 - 2,16). Mass media information on Pap smear was 6,2% and the greater barrier to having a Pap smear periodic practice was the performer’s gender (masculine) (34,2%). Conclusions: Level of knowledge, attitudes and practices in our population are low. The greater level of Pap knowledge is not related to correct practice. There is poor diffusion on Pap smear by the mass media. Observations on not having a Pap periodic practice are mainly psychological.